Developing reading comprehension assessment: flashcard assessment media for junior high school student - Mu'ammalatun, Astuti; Wahyuni, Sri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to develop a reading comprehension assessment tool using flashcard media for 9th-grade junior high school students, based on the ADDIE model. The development process of the flashcards began with a needs analysis to identify challenges in reading comprehension among students. The developed flashcards include various question types aligned with curriculum standards and were validated by experts to ensure their accuracy, clarity, and appeal. The trial involved a reading test consisting of 25 choice questions. The analysis results showed that the majority of the items (80%) were valid and suitable for assessing students' comprehension, while 20% required revision. Additionally, the reliability analysis yielded a Cronbach's Alpha value of 0.839, indicating high internal consistency. This study concludes that flashcards, as an assessment tool, are effective and reliable in improving reading comprehension among 9th-grade junior high school students.